Naturaleza. (Buenos Aires, Argentina : Sigmar, 1994)
Photographs and text depict elements of nature, such as plants, birds, insects, and other animals, in their various natural settings.
"Un libro Dorling Kindersley"--P. facing t.p.
Keywords: Nature; Animals; Plants; Spanish language materials